Loss of trabeculae by mechano-biological means may explain rapid bone loss in osteoporosis. - Prendergast, Patrick John (My University, 2008)
Osteoporosis is characterized by rapid and irreversible loss of trabecular bone tissue leading to increased bone fragility. In this study, we hypothesize two causes for rapid loss of bone trabeculae; firstly, the perforation of trabeculae is caused by osteoclasts resorbing a cavity so deep that it cannot be refilled and, secondly, the increases in bone tissue elastic modulus lead to increased propensity for trabecular perforation. These hypotheses were tested using an algorithm that was based on two premises: (i) bone remodelling is a turnover process that repairs damaged bone tissue by resorbing and returning it to a homeostatic strain level and (ii) osteoblast attachment is under biochemical control. It was found that a mechano-biological algorithm based on these premises can simulate the remodelling cycle in a trabecular strut where damaged bone is resorbed to form a pit that is subsequently refilled with new bone. Furthermore, the simulation predicts that there is a depth of resorption cavity deeper than which refilling of the resorption pits is impossible and perforation inevitably occurs. However, perforation does not occur by a single fracture event but by continual removal of microdamage after it forms beneath the resorption pit. The simulation also predicts that perforations would occur more easily in trabeculae that are more highly mineralized (stiffer). Since both increased osteoclast activation rates and increased mineralization have been measured in osteoporotic bone, either or both may contribute to the rapid loss of trabecular bone mass observed in osteoporotic patients
PUBLISHED
Keywords: bone loss; mechano-biology